(untitled) (Eurasian Journal of Engineering and Technology, 2025)
This scientific article explored the theoretical and methodological foundations for improving the managerial competencies of vocational education institution leaders in the context of digital transformation. Within the scope of the research, the essence of key concepts such as "managerial competence," "digital transformation," and "innovative approach" was critically analyzed, and authorial definitions were proposed. The transition of management theories from a traditional-administrative approach to a digital leadership paradigm was substantiated. As a result of synthesizing conceptual frameworks developed by international organizations (UNESCO, OECD, World Bank) and advanced theories (distributed leadership, inside-out improvement), an updated threecluster structure of leader competencies was formed. This structure includes strategictechnological, innovative-adaptive, and humanistic-collaborative competencies. The analysis identified the structural components and key indicators for each competency cluster.